Delayed Capillary Flow of Elastomers: An Efficient Method for Fabrication and Nanofunctionalization of Flexible, Foldable, Twistable, and Stretchable Electrodes from Pyrolyzed Paper - Damasceno, Sergio [UNESP]; Corrêa, Cátia Crispilho; Gouveia, Rubia Figueredo; Strauss, Mathias; Bufon, Carlos César Bof [UNESP]; Santhiago, Murilo (Wiley, 2020)
Pyrolyzed cellulose-based materials are extensively used in many fields for many different applications due to their excellent electrical properties. However, pyrolyzed materials are extremely fragile and prone to crack. To address this issue, a new fabrication method is reported to delay the capillary flow of elastomeric materials into the porous structure of the paper. By changing the surface chemistry and porosity of the material, the capillary flow of the elastomer through the porous structure is delayed. Delayed capillary flow of elastomers (DCFE method) ensures both extremely high mechanical stability and electrochemical performance to the devices. Impressively, the electrochemical devices can be bent, folded, twisted, and stretched at 75% of their original length without hindering their electrochemical response. Moreover, cooperative nanofilms are prepared using a co-deposition process with Meldola's blue (MB) and polydopamine (PDA). While MB guarantees electrocatalytic properties toward nicotinamide adenine dinucleotide (NADH) electrooxidation, PDA increases the wettability of the surfaces and contribute to addressing hydrophobicity issues of elastomer-based devices. Remarkably, the nanofilms have unprecedented properties by self-collecting aqueous liquids. Furthermore, extreme mechanical tests do not impact the electrochemical performance of the nanofilms.
Keywords: flexible electrodes; nanofilms; polydopamine; pyrolyzed paper; stretchable electrochemical devices